(untitled) (Archives of Criminology, 2023)
Contemporary discussions on the role of populism in criminal justice reform have centred around its potential for more punitive outcomes i.e., longer sentences, less hospitable prison conditions and a lack of meaningful support for integration back into the community. Reflecting on this legislative trend, Julian V. Roberts et al. (2002) opined that a change of posture might be required by proponents of penal reform, going on the offensive and pointing to the negative actions taken by politicians in the name of penal populism. This paper asks whether politicians advocating for less punitive criminal justice reforms in New Zealand could themselves draw from a more populist style of politics. We hypothesise that research participant support for a free-market populist-style argument on decarceration will be higher than for a status quo-style argument. This is examined through a quantitative approach involving the development of an experimental tool that distils the theoretical conceptualisations of populism and tests them on the New Zealand voting-age public. We find through sub-group analysis that a statistically significant number of participants who self-identified as “right” on the political spectrum or voted for either the National party (a major centre-right political party) or the New Zealand First party (a minor conservative political party) in the 2017 New Zealand general election were more inclined to support arguments for less punitive sentences when pitched using a populist-style argument.